Migratory interactive applications for ubiquitous environments - Paternò, Fabio (Human-Computer Interaction Series, 2011)
Ubiquitous environments should provide users with the ability to freely move about while interacting through a  variety of interactive devices (including cell phones, PDAs, desktop computers, digital television sets, and intelligent watches) without losing continuity. A big source of frustration for users is having  to start a session over again from the beginning at each interaction device change. Migratory interactive services can overcome this limitation and support continuous task performances with the ability to adapt to the changing context of use. This comprehensive review with chapters written by authors working in various academic and industrial centres opens with an overview of what to migrate and what adaptation opportunities are available from a mobile operator perspective, before outlining the state-of-the-art from various perspectives. This sets the scene for more detailed coverage of the design of platforms and tools able to support migration, distinguishing between the support for user interfaces, networks and protocols, and application logic. Applications for migration, games and emergency scenarios are outlined, and the book concludes with an assessment of usability and programmability in migratory interactive applications. Researchers in pervasive information systems and ubiquitous environments, HCI, user interfaces, software engineering, middleware, programming and operating systems, as well as interactive service developers and providers for ubiquitous environments will find much to interest and inspire them in this book.